2020
DOI: 10.1002/ijfe.1819
|View full text |Cite
|
Sign up to set email alerts
|

Momentum profits: Fundamentals or time varying unsystematic risk

Abstract: This paper examines how fundamentals and time varying unsystematic risk can explore the origins of momentum strategies. Our data encompasses the monthly returns of listed stocks on the NASDAQ 100 index from 2002 to 2016. The results indicate that winners and losers are slanted towards small‐capitalization stocks with high systematic risk. Whereas only winners have growth and value the characteristics. Additionally, the results from the E‐GARCH‐M indicate that the speed of adjustment to volatility shocks is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Our paper contributes to the literature by providing a new explanation of the distress puzzle as documented by Campbell et al (2008) and dissecting anomalies (Barahona et al, 2021;BenMabrouk & Souayeh, 2021;Jiang et al, 2021). Da and Gao (2010) found that illiquidity was positively associated with high distress risk.…”
Section: Distress Risk Premium Across Limit Of Arbitrage In Longer Ho...mentioning
confidence: 60%
“…Our paper contributes to the literature by providing a new explanation of the distress puzzle as documented by Campbell et al (2008) and dissecting anomalies (Barahona et al, 2021;BenMabrouk & Souayeh, 2021;Jiang et al, 2021). Da and Gao (2010) found that illiquidity was positively associated with high distress risk.…”
Section: Distress Risk Premium Across Limit Of Arbitrage In Longer Ho...mentioning
confidence: 60%